Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/22925503211024871
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia and Preoperative Deep Venous Thrombosis and Their Effect on Free Flap Survival: A Scoping Review

Abstract: Background: A proper preoperative planning is essential to prevent flap failure. However, venous workup for flaps has not been commonly performed or utilized as a preoperative screening tool. A scoping review was conducted to explore preoperative venous system screening, including deep vein thrombosis diagnosis, and its effect on flap survival rate. This review identified existing gaps of knowledge and emphasized potential research areas for future studies. Methods: Two independent reviewers searched 3 electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Hypercoagulability is particularly likely in trauma patients, as a period of increased bleeding from the initial injury due to the consumption of coagulation factors and hemodilution is followed by a pro-coagulant phase. A diagnosis of post-traumatic hypercoagulability is difficult, as no standardized test has been established to evaluate it (22), and although observational studies have shown that coagulation assays such as thromboelastography (TEG®) and rotational thromboelastometry (ROTEM®) have been beneficial in the management of post-traumatic thrombosis, a systematic review of randomized trials showed limited supporting evidence (23). There is therefore a strong indication for developing an established method of post-traumatic thrombus screening preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercoagulability is particularly likely in trauma patients, as a period of increased bleeding from the initial injury due to the consumption of coagulation factors and hemodilution is followed by a pro-coagulant phase. A diagnosis of post-traumatic hypercoagulability is difficult, as no standardized test has been established to evaluate it (22), and although observational studies have shown that coagulation assays such as thromboelastography (TEG®) and rotational thromboelastometry (ROTEM®) have been beneficial in the management of post-traumatic thrombosis, a systematic review of randomized trials showed limited supporting evidence (23). There is therefore a strong indication for developing an established method of post-traumatic thrombus screening preoperatively.…”
Section: Discussionmentioning
confidence: 99%